2001
DOI: 10.1054/bjoc.2000.1556
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cancer and parental use of tobacco: findings from the inter-regional epidemiological study of childhood cancer (IRESCC)

Abstract: Summary Parental smoking data have been re-abstracted from the interview records of the Inter-Regional Epidemiological Study of Childhood Cancer (IRESCC) to test further the hypothesis that paternal cigarette smoking is a risk factor for the generality of childhood cancer. Reported cigarette smoking habits for the parents of 555 children diagnosed with cancer in the period 1980-1983 were compared, in two separate matched pairs analyses, with similar information for the parents of 555 children selected from GP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 24 publications
3
58
0
3
Order By: Relevance
“…The significant trends observed by Sorahan et al (2001) and did not diminish when adjusted for potential confounding covariates or with simultaneous analysis of parental smoking habits. The relationship between maternal smoking and birth weight reported by Sorahan et al (2001) suggested that self-reported maternal smoking was equally reliable for cases and for controls.…”
Section: (B) Bias and Confoundingmentioning
confidence: 83%
See 4 more Smart Citations
“…The significant trends observed by Sorahan et al (2001) and did not diminish when adjusted for potential confounding covariates or with simultaneous analysis of parental smoking habits. The relationship between maternal smoking and birth weight reported by Sorahan et al (2001) suggested that self-reported maternal smoking was equally reliable for cases and for controls.…”
Section: (B) Bias and Confoundingmentioning
confidence: 83%
“…Paternal smoking before pregnancy showed no association with leukaemia risk for any smoking category. Sorahan et al (2001) reported a nonsignificant positive association between risk for acute lymphoblastic leukaemia and daily cigarette smoking by fathers before pregnancy, and a non-significant inverse association between risk for acute lymphoblastic leukaemia and daily smoking by mothers before pregnancy. Down Syndrome children are highly susceptible to the development of acute leukaemia.…”
Section: (A) Duration and Intensity Of Exposurementioning
confidence: 95%
See 3 more Smart Citations